Working At Night The Temporal Organisation of Labour Across Political and Economic Regimes - Dušková, Lucie; Duijzings, Ger (De Gruyter, 2022)
The night has always and almost universally represented a special 'out of the ordinary' temporal zone with its own meanings, possibilities, and dangers. It is only since the modern era that the night has become increasingly 'normalised'. Although 24/7 industrial production is often seen as a consequence of capitalist expansion, other political and economic regimes adopted the 'night shift', normalising it as part of an alternative modernity.